Infraspecific morphological and genome size variations in Linum glaucum in Iran - SEYED MEHDI TALEBI; MASOUD SHEIDAI; MORTEZA ATRI; FARIBA SHARIFNIA; ZAHRA NOORMOHAMMADI (Society for Indonesian Biodiversity, 2015)
Talebi SM, Sheidai M, Atri M, Sharifnia F, Noormohammadi Z. 2015. Infraspecific morphological and genome sizevariations in Linum glaucum in Iran. Biodiversitas 16: 69-78. There are many discussions about taxonomic position of Linum glaucumin different Flora. In this study, the morphological traits associated with the nuclear genome size were used for identification ofinfraspecific variations in the nine populations of L. glaucum. Twenty three qualitative and quantitative morphological characteristicswere investigated. The Analysis of variance tests showed significant difference for some morphological features. The CanonicalCorrespondence Analysis of habitat ecological factors showed that each of the habitats had prominent characteristics, and also Pearson’scoefficient of correlation confirmed the significant correlations between the morphological features in relation to ecological factors. Inthe morphological Unweighted Paired Group using Average method tree, populations were separated from each other, so that populationNo. 4 was separated from others. In the flow cytometery investigations, variation of about 1.19 times was presented between themaximum and minimum averages of the genome sizes in the populations. Minimum amount of genome size was found in populationsNo. 4. Significant correlations occurred between the nuclear genome size with habitat elevation as well as some of the quantitativemorphological features. The mentioned variations caused to difference between the populations and lead to creation of ecotype andecophene in the studied populations.